Health Behaviours of Patients with Circulatory Insufficiency Aged 60-75, treated in the Cardiology Department - Ewelina Bąk; Elżbieta Skowronek (Kazimierz Wielki University, 2018)
Introduction: Heart failure is an important public health problem in industrialized countries with aging populations. The progressive nature of the disease entails a lot of limitations and has an impact on the health behaviour of patients. The aim of this paper was to present health behaviours using the example of patients with cardiac insufficiency treated in the Department of Cardiology of the Railway Hospital in Wilkowice. Materials and methods: The research was carried out by means of diagnostic survey. The research tools involved: a self-questionnaire and a standardized questionnaire of Health Behaviour Inventory. The research was conducted from March to December 2017 among 100 patients hospitalized in the cardiology department, the Independent Public Health Care Centre of the Railway Hospital in Wilkowice - Bystra. Research findings: Among the preferred health behaviours of patients with heart failure, Positive Mental Attitude and Health Practices were the highest rated, and the lowest rated were the correct eating habits. Conclusions: The declared health behaviours, among patients with heart failure, receive higher scores in a statistically significant way, among women, people with higher education, following medical/nursing recommendations and non-smokers.